Porous Asphalt Innovation: Evaluation of Marshall Characteristics of Porous Asphalt with Marble Waste as an Additive - M. Sa'dillah; Blima Oktaviastuti; Marselinus Risaldo Lensa (Jurnal Teknik Sipil dan Lingkungan, 2025)
Transportation is crucial to Indonesia's development, with highways being the main element. Road damage is often caused by low-quality materials, loads, and weather. The modification of asphalt mixtures with additives can improve their stability. Porous asphalt, which is effective in terms of drainage and strength, can improve the road safety. In Tulungagung, marble waste can be used in asphalt mixtures, thereby reducing waste and cost. This study evaluates the use of marble waste in asphalt mixtures, particularly the characteristics of the porous asphalt Marshall. The method used was The Australian Asphalt Pavement Association (AAPA) Marshall with stability parameters, Flow, Voids in Mix (VIM), Voids in Mineral Aggregate (VMA), Cantabro Loss (CL), and Asphalt Flow Down (AFD), with variations in asphalt content of 4.5, 5, 5.5, and 6%. After obtaining the OAC, the test specimens were made with marble fragments and marble powder contents of 15, 25, and 35%. The results showed that the OAC was 5% with Marshall characteristics, namely stability of 1,037 kg, flow of 3.33 mm, Marshall quotient of 311 kg/mm, VIM of 24.96%, and VMA of 27.84%wasmarble frMarshallat a content of 25% Marshall characteristics are stability 509 kg, flow 3.00 mm, Marshall quotient 200 kg/mm, VIM 19.00%, and VMA 50.00%. and marble powder at 15 % content is stability 805 kg, flow 3.00 mm, Marshall quotient 279 kg/mm, VIM 27.00% and VMA 40.00%. All parameters meet the specifications except VIM, which does not meet the specifications because the addition of marble powder reduces voids in the porous asphalt. The AFD value decreases with an increasing percentage of marble fragments and marble powder, affecting the separation of asphalt in the mixture and the permeability value.